The process of implementing a politics of culture in Campinas city (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The objective of the article is to report the experience of the first years of the Council of Public Policy of Campinas. It starts making links between micro and macro policies in the cultural area into a theoretical context, especially in the field of performing arts. The methodology for the research was based on interviews, questionnaires, attendance at Council and at groups meetings and also on the analysis of minutes and recorded meetings. It is concluded that the experience of the Council of Campinas at this moment is as decolonizing of the unconscious as the micropolitics of art.
Keywords: Council of Culture; Municipal System of Culture; Campinas; Participation; Cultural policy